Left ventricular thrombosis and endogenous endophthalmitis in the setting of COVID‐19: A case report - Mohammad Javad Zibaeenezhad; Alireza Moaref; Firoozeh Abtahi; Mohsen Moghadami; Mohammad Karim Johari; Ali Ardekani; Mohammad Keshavarz (Clinical Case Reports, 2022)
Abstract Aside from typical pneumonia, the coronavirus disease 2019 (COVID‐19) has shown several extra‐pulmonary manifestations. This study was done on a 66‐year‐old male patient who concomitantly had endogenous endophthalmitis and left ventricular thrombosis one month after being hospitalized due to COVID‐19.